Conversion of lignocellulosic materials from local grass to bioethanol - Liong, Yan Yee (2012)
Grass is a candidate biomass producer because it is fibrous and it thrives growing on poor soil. The chemical properties of two grass species growing naturally and abundantly in idle lands in Malaysia were investigated. Grass selected were ‘Lalang’ (Imperata cylindrica) and Napier grass (Pennisetum purpureum). For the analysis, Napier grass was further divided into male and female plants, and stem and leaves. Lignin, hemicellulose and cellulose contents were determined using the TAPPI standard methods. ‘Lalang’ appeared not to be an attractive biomass producer because of its high lignin content (22%). On the contrary, Napier grass, particularly the female stem had low lignin content (13%) and a favorably high level of cellulose (46%). In female leaf, lignin content was higher (20.7%) while cellulose (30.4%) was lower, when compared to the stem. Although cellulose content in the male stem (51%) was slightly higher than the female, its lignin was two-fold above that of the female stem, making it a less desirable biomass producer. With the results obtained it was concluded that female Napier grass in Malaysia has a good potential of becoming a biomass producer. Female Napier grass, the best grass candidate was selected to undergo two different pretreatments, alkali pretreatment and biological pretreatment. Alkali pretreatment was carried out at four different NaOH concentrations: 1%, 5%, 7% and 10%. Alkali pretreated materials were subjected to Trichoderma reesei ATCC 26921 enzyme hydrolysis; several hydrolysis parameters were tested to optimize glucose yield including temperature and agitation, by applying the Response Surface Method (RSM). HPLC revealed that samples pretreated with 5% NaOH had glucose content of 7.47g/L and 7 % NaOH yielded glucose content of 7.4g/L. There was no difference between 5% and 7% NaOH pretreated material. However between the two, 7 % NaOH can be considered as a better pretreatment because the glucose yield was consistent throughout the parameters of temperature and agitation; these two parameters can affect the optimum activity of cellulase in converting cellulose to glucose. From RSM analysis, glucose yield was optimal at 38.5˚C and 175rpm. When using the whiterot fungus, Phanerochate chrysosporium as biological pretreatment, followed by Trichoderma reesei ATCC 2692 enzyme hydrolysis at constant enzyme loading of 1ml with 1g of material, samples pretreated for three weeks gave the highest glucose yield (4.5g/L). However, the yield was lower than the alkali pretreated grass. On looking at the efficiency of these two pretreatments, alkali pretreatment was a better pretreatment as it yielded higher glucose content compared to biological pretreatment, despite the ease of handling and time consuming of the experiment conducted. Hydrolysates from the pretreatments were fermented using the ethanol insensitive strain Escherichia coli K011 at 35˚C and 100rpm, and the ethanol content was detected by Gas Chromatography (GC). After 24 hours of fermentation, alkali pretreated material yielded 37.7% ethanol while biological pretreated material yielded 24.4% ethanol. It was observed that alkali pretreated grass material gave out higher ethanol yield. These results indicated that Malaysia’s female Napier grass is capable of becoming an important biomass for producing bioethanol.